Cross-Contamination as a Problem in Collection and Analysis of Environmental Samples Containing Microplastics—A Review - Aleksandra Bogdanowicz (MDPI AG, 2021)
Research conducted so far on the presence of microplastics in the environment shows that these items are ubiquitous pollutants and therefore constitute an inherent part of our lives. This constitutes a significant problem in many aspects, and one of them is the correct identification of microplastics in environmental samples. Environmental samples can be easily contaminated by plastic microparticles from other sources if proper precautions are not taken during sampling and analysis. The consequence of not taking this cross-contamination into account when analysing the results may be their significant overestimation. This review aims to draw attention to the problem of cross-contamination that accompanies the collection and analysis of samples for the presence of microplastics, and to discuss this issue in a comprehensive manner. The article indicates potential sources of cross-contamination, lists the mitigation methods, and describes the possibilities of assessing this type of contamination. Moreover, the review examines how cross-contamination control appears in practice, based on the available literature data.